Simulation of spinning soccer ball trajectories influenced by altitude - Hörzer, S.; Fuchs, C.; Gastinger, R.; Sabo, A.; Mehnen, L.; Martinek, J.; Reichel, M. (Procedia Engineering, 2010)
In soccer, the ball is affected by aerodynamic forces and consequently by altitude. Therefore, the objective of this paper was to simulate the influence of the altitude of the different venues of the FIFA Soccer World Cup 2010 based on trajectories of a spinning soccer ball. To simulate the ball's trajectories a free kick scenario with constant launch conditions was used, implemented with an iterative solving algorithm. The results showed that altitude influenced different flight parameters such as velocity, spin parameter or final position at the soccer goal which can have a major effect on goal scoring.